Production and quality parameters of three banana cultivars FHIA-17, FHIA-25 and Yangambi - Brenes-Gamboa, Saúl (Agronomía Mesoamericana, 2017)
The objective of this work was to determine indicators of growth, development, fruit characteristics, and organoleptic properties of banana FHIA-25, FHIA-17, and Yangambi cultivars. Five lots were chosen in different farms in the town of Turrialba, Costa Rica, during the years 2013 and 2014. Each lot contained 30 plants of each kind. Coco and Congo cultivars were included in the analysis of fruit and organoleptic properties since they have local importance as well. The FHIA-25 showed vigor and resistance to black Sigatoka, had a greater number of fruit bunches (13.8), and increased more than 47 kilograms the fruits weight. The highest brix degree level was obtained with the Gros Michel, which was the material that was used as a reference and which is traditionally grown in the area. Although FHIA-25 showed great agronomic performance, it just reached 17 brix degrees at the peak of its ripeness. Regarding consumers’ taste and preferences , 37% of interviewees said that FHIA-17 tasted well. The inclination towards Gros Michel was always higher; in addition to the aforementioned this type of analysis encourages seeking for new alternatives instead of relying on cultivars of this subgroup in order to satisfy the demand for this fruit for both fresh consumption and industry purposes.